2013
DOI: 10.4238/2013.january.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine used as an acesodyne in human breast cancer therapy causes an undesirable side effect, upregulating anti-apoptosis protein Bcl-2 expression

Abstract: ABSTRACT. Ketamine is a dissociative anesthetic agent that has been widely used in surgery and for relieving pain in chronic cancer patients. We applied ketamine to breast cancer cell line MDA-MB-231 to detect the effect of treatment and molecular mechanisms involved. We found that ketamine can upregulate the level of anti-apoptosis protein Bcl-2, which promotes breast cancer cell invasion and proliferation. Knockdown of Bcl-2 could inhibit the increase of Bcl-2 and reduce the invasion and proliferation caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The benefit for patients with colorectal cancer with advanced disease by repressing WNT through ADNP induction with low-dose ketamine may quite easily be tested as an add-on to existing treatment regimens, as this substance and its pharmacologic characteristics are well studied (30). Of course, side effects of this treatment are to be carefully evaluated and strictly balanced with potential therapeutic benefits, especially since others reported adverse effects of ketamine for patients with other malignancies, such as breast cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit for patients with colorectal cancer with advanced disease by repressing WNT through ADNP induction with low-dose ketamine may quite easily be tested as an add-on to existing treatment regimens, as this substance and its pharmacologic characteristics are well studied (30). Of course, side effects of this treatment are to be carefully evaluated and strictly balanced with potential therapeutic benefits, especially since others reported adverse effects of ketamine for patients with other malignancies, such as breast cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…While another recent studies found that the preoperative administration of 0.5 mg/kg ketamine in patients undergoing cesarean section did not elicit a preemptive analgesic effect 13 . Moreover, Hala et al 14 reported that intranasal ketamine could enhance the postoperative analgesia after endoscopic nasal surgery, but the psychomimetic side effects of ketamine still occurred with intranasal administration. Thus, whether preemptive analgesic of ketamine is effective and safety in managing postoperative pain remains need more strong evidence to determine.…”
Section: Introductionmentioning
confidence: 99%
“…He et al reported that ketamine could induce anti-apoptotic protein Bcl-2 upregulation and promote breast cancer cell invasion and proliferation. 41 Contrastingly, a recent study suggested that ketamine was an N-methyl-D-aspartate (NMDA) antagonist that inhibits pancreatic cancer cell proliferation and apoptosis. 42 These indicate that ketamine has cancer-promoting effects mainly involving immune function suppression; however, its direct effect on cancer cells remains unclear.…”
Section: Ketaminementioning
confidence: 99%